Управління стратегічно-орієнтованим портфелем інноваційних проектів модернізації обладнання енергопідприємства - Саченко, Олег Анатолійович (НТУ "ХПІ", 2017)
Виконано оцінку семи основних процедур управління портфелем згідно міжнародного стандарту ISO 21504 і визнано доцільним більш детально проаналізувати дві процедури: 1) перевірка відповідності портфеля стратегічним цілям; 2) балансування та оптимізація портфеля. Запропоновано ввести в процес управління портфелем компетентну особу (портфельного менеджера) як для забезпечення безперервного стратегічного узгодження портфеля інноваційних проектів на енергопідприємстві, так і збалансування і контролю за портфелем. Розглянуто основні аспекти реалізації стратегічно-орієнтованим портфелем інноваційних проектів модернізації обладнання енергопідприємства на прикладі енергокомпанії.

The evaluation of the seven basic portfolio management procedures was done according to the international standard ISO 21504 and it was recognized for greater efficiency to do the detailed analysis of two procedures: 1) the verification of the correspondence the portfolio to strategic objectives of the power company; 2) the balancing and the optimizing for portfolio. Also, it is proposed to apply in the portfolio management process the competent person (portfolio manager) for security of continuous strategic coordination for portfolio of innovative projects in power company for the balancing and controlling the portfolio. Recommendations for implementation of the strategically oriented portfolio of innovative projects for equipment modernization of the power company are performed too.
Forming of strategically-oriented portfolio of innovative projects for electric power equipment modernization
Keywords: енергопідприємство; інноваційний проект; концептуальна модель; модернізація обладнання; портфель проектів; стратегія управління; управління проектами; utilities; innovative design; conceptual model; upgrading equipment; project portfolio; strategy management; project management